Cyanoacrylate glue for iatrogenic retinal breaks during vitrectomy in stage 5 familial exudative vitreoretinopathy - Zou, Yihua; Peng, Jie; Zhao, Peiquan (Frontiers in Medicine, 2024)
Purpose: To describe the role of cyanoacrylate glue in sealing iatrogenic retinal breaks (IRBs) during vitrectomy in stage 5 familial exudative vitreoretinopathy (FEVR) with funneled retinal detachment (RD).Methods: Nine eyes of nine patients diagnosed as stage 5 FEVR were treated with cyanoacrylate glue for IRBs during vitrectomy from July 2020 to January 2022. The clinical records, including patient information, surgical process, and follow-up examinations, were collected retrospectively. Anatomical outcomes and visual outcomes were summarized.The average age at surgery was 19.6 months (range: 3.8 -41.1 months). The mean post-operative follow-up period was 12.5 months (range: 9.8 -18.8 months). Before surgery, five eyes had an open-funnel RD and four eyes had a closed-funnel RD. All the preretinal fibroplasia membranes were removed as thoroughly as possible in the nine eyes. IRBs formed at the posterior pole in two eyes and peripheral retina in seven eyes. All the IRBs were sealed successfully by the cyanoacrylate glue when they appeared. At the final post-operative visit, eight eyes had partial retinal reattachment without progression of fibroplasia tissues, while one eye had total retinal redetachment. The rate for stable anatomical outcome was 88.9% (8/9) in this study. The visual testing available for seven eyes demonstrated light perception in five eyes and no light perception in two eyes. No severe perioperative glue-related complications were noted during the follow-ups.The application of cyanoacrylate glue may be an alternative therapy for IRBs in stage 5 FEVR surgeries, while the long-term efficacy and safety still need further investigation.